The political in art. A contribution from the theory of Jacques Rancière - Capasso, Verónica Cecilia (Estudios de Filosofía, 2018)
In this paper we propose to make a contribution to the field of sociopolitical studies of art, based on a critical review of Jacques Rancière’s proposal. The theory of the aesthetics of this author has renewed –along with the proposals of other theoreticians– the modern view of the relationship between art and politics, raising the political in art from a reading that is not confined to the subject of the work. It is intended not only a descriptive review of the contents and arguments of Rancière, but also to see the weaknesses and strengths of his proposals. Thus, once the analysis exposed, it will be productive for the development of future research aimed at the study of artists and groups of artists of different origin and temporality, which expand the current horizons and glimpse the power of art to intervene in the transformation of the social order.